BOOK REVIEW: WILLIAM SHAKESPEARE, “SONNETS/SONETE: O NOUĂ VERSIUNE ROMÂNEASCĂ”, TRANSLATED BY CRISTINA TĂTARU. CLUJ-NAPOCA: LIMES, 2011, 315 P. - Diana MELNIC; Vlad MELNIC (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
To translate poetry of any kind always takes a certain amount of courage on behalf of the translator. Indeed, some argue that the poetry itself is precisely what is lost in the process, yet, as Allen Tate once famously stated, translation remains “forever impossible and forever necessary.” This is particularly the case with Shakespeare’s sonnets, a kind of poetry riddled with rhetorical devices, powerful imagery, as well as figures of speech such as similes, metaphors, and synecdoche, all of which confer to it its aesthetic quality, but are, at the same time, nearly impossible to isolate from their source language. Furthermore, while Shakespeare did write about ageless themes, including love, lust, the brevity of life, or the impermanence of beauty, his sonnets are nevertheless deeply rooted in their time by means of clever uses of intertextuality and the nuances of a sixteenth century, rural Stratfordean parlance.